A internacionalização do Instituto Federal de Educação, Ciência e Tecnologia de São Paulo (IFSP) - Bassoli, Marcos Gabriel (Universidade Federal de São Carlos, 2018)
The internationalization of educational policies is a relevant theme, especially considering the constant changes in the international system. On this way, this dissertation aims to analyze how the process of internationalization of the Federal Institute of Education, Science and Technology of Sao Paulo has occurred, by mapping and verifying its institutional and structural aspects to better visualize the spaces, paths and opportunities of the institution. For this purpose, the research relied primarily on the historical survey related to the origins of brazilian technical and technological education system, in order to identify the origins and peculiarities of this institution for later observation of its characteristics in relation to the international insertion. In the sequence, the study was based on the analysis of the purposes and causes of the international cooperation for the development and in what forms the thematic of the education is introduced in this context, also looking for the actual position of the Brazilian internationalization of superior education. The third and last part had the specific goal to analyze how IFSP's international insertion actions have been processed to the date, describing its institutional characteristics and program coverage, culminating in conclusions about the potentialities and possible paths to be followed by this government entity.
Keywords: IFSP; Internacionalização da educação; Cooperação internacional; Internationalization of education; International cooperation; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICA INTERNACIONAL; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO::INSTITUICOES GOVERNAMENTAIS ESPECIFICAS; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::HISTORIA DA EDUCACAO; OUTROS::RELACOES INTERNACIONAIS